Vegetable production and marketing in Africa [ socio-economic research - Mitho¨fer, Dagmar (CABI, 2011)
This book provides a collection of conceptual and methodological chapters on the socio-economic aspects of vegetable production-to-marketing systems in Africa. The diverse topics covered in this book include the conceptual challenges in economic researc on vegetable production systems, the implications of good agricultural practice standards, the challenges and opportunities of meeting the growing market demand and issues in pest management. The book aims to inform researchers, development partners and policy makers on the opportunities and constraints of vegetable production-to-marketing systems for development. The book has 16 chapters and a subject index.